High tech vs high touch? ; Cross country analysis of online banking service quality in South Africa and Indonesia / Nuri Wulandari, Johan W de Jager and Elizma Wannenburg - Wulandari, Nuri; de Jager, Johan W; Wannenburg, Elizma (UiTM Cawangan Johor, 2019)
Online banking has been an important instrument to keep up with today’s digital savvy customers. Performing the best in this area can elevate the competitive advantage of banks in the industry to a higher position. The study is initiated by the understanding that it is crucial to ensure that the service quality of online banking matches up the expectation of the banks’ customers. The objectives of the study is to evaluate and investigate the perception of customers on Online Banking service quality of banks in South Africa (SA) and Indonesia (INA). A survey was conducted resulting in a total 342 respondents from both countries. The result revealed that each of the countries have different emphasis, one is focusing on being ‘high tech’ and the other excels in their’ high touch’ approach. The study has also found significant differences between the perceptions of both SA and INA’s banking customers. The uniqueness of the study is that the perceptions of banking customers in two developing countries are being compared. The paper concludes with practical implications and suggestions for future research for the banking industry in both countries.